Effect of Silver Nanoparticles on distribution of Certain Trace Elements in Various Organs of Normal and Gamma Irradiated Rats (Journal of Nuclear Technology in Applied Science, 2019)
The present study was performed to evaluate the effect of 28 days subchronic oral administration of AgNPs in normal and irradiated (4 Gy) rats on the distribution of certain trace elements (silver (Ag), zinc (Zn), copper (Cu), iron (Fe), calcium (Ca), magnesium (Mg) and manganese (Mn) contents in various organs tissues including liver, kidney, lung and testes. AgNPs were orally administered daily for 28 days continuously and the vehicle as well in the vehicle group. The study was performed to investigate the effect of AgNPs on trace elements in different organs and as compared with irradiated treated AgNPs group. Results of the present study demonstrated that subchronic oral administration of AgNPs (26.878 mg/kg b. wt.) induced changed in the concentration of the estimated essential elements in the various tissues examined of normal rats. The recorded changes in the tested trace elements pointed to (Zn), (Fe) and (Ca) content in liver, kidney, lung and testes tissues. Radiation exposure (4Gy) of rats produced marked alterations in the distribution of tested trace elements in all tissues investigated of irradiated rats, concerned with (Zn), (Cu), (Fe), (Ca), (Mg) and (Mn) in liver, kidney, lung and testes tissues. Combined exposure to γ-radiation (4Gy) and AgNPs (42.599 mg/kg b. wt.) treatment showed marked variation in trace elements content of (Zn), (Cu), (Fe), (Ca), (Mg) and (Mn) of the selected tissues examined. Such variations were more or less pronounced than the individual effects of either AgNPs treatments or γ-radiation exposure. The detected variation in the concentrations of the estimated trace elements of various tested organs might be attributed to the selective responsiveness of each tissue to the combined effect of both AgNPs treatment and γ-radiation. In conclusion, AgNPs administration after γ-radiation has considerate effect on the levels of metals in liver and lung tissues which give attention that these organs more sensitive to AgNPs.
Keywords: AgNPs; γ-radiation; iron; zinc; calcium